Synthesis of a Targeted Library of Heparan Sulfate Hexa‐ to Dodecasaccharides as Inhibitors of β‐Secretase: Potential Therapeutics for Alzheimer's Disease. Issue 21 (3rd April 2013) - Schwörer, Ralf; Zubkova, Olga V.; Turnbull, Jeremy E.; Tyler, Peter C.
Abstract Heparan sulfates (HS) are a class of sulfated polysaccharides that function as dynamic biological regulators of the functions of diverse proteins. The structural basis of these interactions, however, remains elusive, and chemical synthesis of defined structures represents a challenging but powerful approach for unravelling the structure–activity relationships of their complex sulfation patterns. HS has been shown to function as an inhibitor of the β‐site cleaving enzyme β‐secretase (BACE1), a protease responsible for generating the toxic Aβ peptides that accumulate in Alzheimer's disease (AD), with 6‐O‐sulfation identified as a key requirement. Here, we demonstrate a novel generic synthetic approach to HS oligosaccharides applied to production of a library of 16 hexa‐ to dodecasaccharides targeted at BACE1 inhibition. Screening of this library provided new insights into structure–activity relationships for optimal BACE1 inhibition, and yielded a number of potent non‐anticoagulant BACE1 inhibitors with potential for development as leads for treatment of AD through lowering of Aβ peptide levels.